On Serge Moscovici's 95th anniversary: The theory of social representations - history, postulates and dissemination - Pascal Moliner; Inna B. Bovina (Peoples' Friendship University of Russia (RUDN University), 2020)
The theory of social representations is one of the major theories in social psychology with the thousands of scientific articles that has been published since its birth. In this article we return to the reasons for this success. First, it can be explained by the relative flexibility of the initial postulates of this theory. This flexibility has allowed researchers who are sometimes far removed from psychology to adapt it to their own problems. But the success of the theory of social representations can also be explained by the action taken by Serge Moscovici throughout his career to spread his theory throughout the world. Finally, Serge Moscovici never ceased to suggest new ideas about social representations and many of his suggestions remain untapped to this day. They constitute a real reservoir for researchers of tomorrow.